Looking into the crystal ball: quality of life, delinquency, and problems experienced by young male adults after discharge from a secure residential care setting in the Netherlands - E. A. W. Janssen-de Ruijter; E. A. Mulder; I. L. Bongers; L. Omlo; Ch. van Nieuwenhuizen (BMC, 2019)
Abstract Background Adolescents in residential care are a vulnerable population with many problems in several life areas. For most of these adolescents, these problems persist after discharge and into adulthood. Since an accumulation of risk factors in multiple domains increases the likelihood of future adverse outcomes, it would be valuable to investigate whether there are differences in life after residential care between subgroups based on multiple co-occurring risk factors. Aims and hypothesis The aim of this exploratory follow-up study is to explore differences between young adults-classified in four risk profiles-in relation to life after discharge from a secure residential care setting. It is hypothesised that young adults with a profile with many risks in multiple domains will experience more problems after discharge, such as (persistent) delinquency, compared to young adults with a profile with lower risks. Methods Follow-up data were collected from 46 former patients of a hospital for youth forensic psychiatry and orthopsychiatry in the Netherlands. In order to illustrate these young adults' life after discharge, self-reported outcome measures divided into five domains (i.e., quality of life, daily life, social life, problems, and delinquency) were used. Differences between four classes based on pre-admission risk factors, which were identified in a previous study by latent class analysis, were explored by three (non-)parametric statistical tests. Results Life after discharge for most young adults was characterised by close friends and a high quality of life, but also by substance abuse, professional support, debts, and delinquency. Only a few significant differences between the classes were found, primarily between young adults with risk factors in the individual, family, school, and peer domains and young adults in the other three classes. Conclusions Young adults experience a high quality of life after discharge from secure residential care, despite the presence of persistent problems. Some indications have been found that young adults with risk factors in four domains are at greatest risk for persistent problems in young adulthood. Because of the high amount of persistent problems, residential treatment and aftercare should focus more on patients' long-term needs.